Firewood transport and invasive insect spread in Michigan - Erin Budzyn; Emily S. Huff; Heidi Frei (Frontiers in Forests and Global Change, 2024)
Transportation of firewood can be a vector for invasive insect spread resulting in damage to surrounding areas. In 2016 and 2021, surveys were conducted at campgrounds around Michigan to understand where campers were sourcing their firewood, awareness of the ‘Do not move firewood’ campaign, knowledge of invasive insects and pests, reactions to a potential ban on bringing firewood to campgrounds, and perspective on kiln-dried firewood – all potential policy levers to reduce the spread of invasive insects. Results indicated that campaign awareness slightly decreased between the survey years, personal firewood transport has decreased, and knowledge of invasives remains low. There is an opportunity for intensifying invasive species and firewood outreach efforts, however, regulation (and enforcement) may be more effective among those who would not comply or support a ban.